Bovine Polymorphonuclear Neutrophils Cast Neutrophil Extracellular Traps against the Abortive Parasite Neospora caninum - Villagra-Blanco, Rodolfo; Silva, Liliana M. R.; Muñoz-Caro, Tamara; Yang, Zhengtao; Li, Jianhua; Gärtner, Ulrich; Taubert, Anja; Zhang, Xichen; Hermosilla, Carlos (Frontiers in Immunology, 2017)
Neospora caninum represents a relevant apicomplexan parasite causing severe reproductive disorders in cattle worldwide. Neutrophil extracellular trap (NET) generation was recently described as an efficient defense mechanism of polymorphonuclear neutrophils (PMN) acting against different parasites. In vitro interactions of bovine PMN with N. caninum were analyzed at different ratios and time spans. Extracellular DNA staining was used to illustrate the typical molecules of NETs [i. e. histones (H3), neutrophil elastase (NE), myeloperoxidase (MPO), pentraxin] via antibody-based immunofluorescence analyses. Functional inhibitor treatments were applied to reveal the role of several enzymes [NADPH oxidase (NOX), NE, MPO, PAD4], ATP-dependent P2Y2 receptor, store-operated Ca++entry (SOCE), CD11b receptor, ERK1/2- and p38 MAPK-mediated signaling pathway in tachyzoite-triggered NETosis. Neospora caninum tachyzoites triggered NETosis in a time- and dose-dependent manner. SEM analyses revealed NET structures being released by bovine PMN and entrapping tachyzoites. Neospora caninum-induced NET formation was found not to be NOX-, NE-, MPO-, PAD4-, ERK1/2- and p38 MAP kinase-dependent process since inhibition of these enzymes led to a slight decrease of NET formation. CD11b was also identified as a neutrophil receptor being involved in NETosis. Furthermore, N. caninum-triggered NETosis depends on Ca++ influx as well as neutrophil metabolism since both the inhibition of SOCE and of P2Y2-mediated ATP-uptake diminished NET formation. Host cell invasion assays indicated that PMN-derived NETosis hampered tachyzoites from active host cell invasion thereby inhibiting further intracellular replication. NET formation represents an early and effective mechanism of response of the innate immune system, which might reduce initial infection rates during the acute phase of cattle neosporosis.